2021
DOI: 10.1029/2020ef001965
|View full text |Cite
|
Sign up to set email alerts
|

Coastal Migration due to 21st Century Sea‐Level Rise

Abstract: We provide an estimate of 21 st century global coastal migration due to sea-level rise taking into account local coastal protection.• Using multiple climate and socio-economic scenarios we estimate 21 st century coastal migration to 17-72 million people. 10 • Considering coastal retreat as an option in coastal adaptation decision making low-11 ers 21st century cost of sea-level rise by factors 2 to 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 64 publications
3
36
0
Order By: Relevance
“…SLR‐related hazards could potentially displace tens of millions of people living in coastal areas by the end of this century (Hino et al, 2017 ; Lincke & Hinkel, 2021 ; Nicholls et al, 2011 ). Depending on population growth, more than one billion people could be populating the low‐elevation coastal zone and be vulnerable to SLR‐related hazards (Hauer, 2017 ; Neumann et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…SLR‐related hazards could potentially displace tens of millions of people living in coastal areas by the end of this century (Hino et al, 2017 ; Lincke & Hinkel, 2021 ; Nicholls et al, 2011 ). Depending on population growth, more than one billion people could be populating the low‐elevation coastal zone and be vulnerable to SLR‐related hazards (Hauer, 2017 ; Neumann et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Global warming will cause flooding of productive coastal areas within the next 100 years involving substantial uncertainties and neither easy nor inexpensive solutions (Anderson et al, 2020;Lincke and Hinkel, 2021). The "shifting baseline syndrome" will mark the events (Pauly, 1995;Jones et al, 2020;Thomas, 2020), and regional differences within and beyond national jurisdictions will characterize them.…”
Section: A Narrative -Global Mean Sea-levelmentioning
confidence: 99%
“…Past experience has shown that effective, site-specific coastal planning can mitigate beach erosion and result in a stable coastline; the most prominent example of this is the Dutch coast [48]. While sea level rise results in coastal recession almost everywhere around the world, many locations have ambient erosive trends related to human interventions that could theoretically be avoided by more sustainable coastal and watershed management practices [49,20,50]. At the same time, the magnitude of the projected sea level rise implies unprecedented pressure on our coasts, requiring the development and implementation of informed and effective adaptation measures.…”
Section: Moving Toward Coastal Zone Sand Management Practices At the Sand Cell Levelmentioning
confidence: 99%